Regional white matter lesion load in elderly patients with somatic vs. non-somatic delusional disorder - Wolf, Robert Christian; Schmitgen, Mike; Otte, Marie-Luise; Karner, Martin; Pycha, Roger; Kirchler, Erwin; Wolf, Nadine D.; Huber, Markus (Psychogeriatrics, 2025)
Objective Delusional disorders (DD) are among the most debilitating mental disorders in the elderly. Persistent monothematic delusions frequently include paranoid and persecutory beliefs, as well as various forms of somatic delusions, including delusions of being infested by pathogens. So far, little is known about the neural correlates of DD. Yet, particularly in elderly patients, white-matter lesions (WML) are thought to play an important pathophysiological role. Methods To investigate regional WML in patients with DD, structural MRI was used, followed by automated lesion segmentation methods to facilitate WML load (WMLL) comparisons between healthy controls (HC, n = 28) and patients with distinct types of DD, that is, somatic (n = 16) versus non-somatic DD (n = 17). Patients with somatic DD presented with specific delusional content, that is, beliefs of delusional infestation (DI), whereas individuals with non-somatic DD (non-DI) showed predominantly paranoid and persecutory content. Results Regions with higher WMLL in both DI and non-DI patients compared to HC included the anterior cingulate and lateral prefrontal regions located in the middle frontal gyrus. Regions with higher WMLL in DI patients versus both HC and non-DI patients were predominantly located in the sensorimotor areas of the frontal lobe. Conclusion The data suggest distinct patterns of regional WMLL in elderly patients with DI versus non-DI. The anatomical distribution of WMLL supports a neuromechanistic model that emphasises the importance of brain areas that drive the internal bodily focus of somatic delusions versus the externalised cognitive distortions that can be observed in non-somatic delusions.